(3GdLhGgQ GdNeSs - (3GHf NWjQ GdOjf , eMeO Hf NWjQ Hf HGjRjO GdYWGQ, CHh GdeDjO,J (B970 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCMO GdUeO GdaQO GdPi de jdO hde jhdO MeOkG HdG HOGjI hKfGA HdG fgGjI s
(3BNQgG (B:s
(3ChdFc CYXe OQLI ef GdPjf jDefhf , hUd Ydi fHjc hNdjaJc ai NdjaJc hBdg GdWjHjf GdWGgQjf HQMeJc jG CQMe GdQGMejf bO JeJ GdLhGgQ GdNeS s
(3HgG fXGe GdJYbjHIs
(3jdGMX Cf gPg GdfSNI JfbU Yf GdfSNI GdSGHbI HQbe (B5 (3ebOGQ UaMI ai BNQgG JTJed Ydi OYGAs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B282s
Keywords: (3GdMQha h GdChaGbs